Peran Kesadaran Diri dan Keterlibatan Apel Pagi dalam Meningkatkan Disiplin Kerja ASN - Kusuma, Rhendra; Wijono, Hani Adi (Jayapangus Press, 2025)
This study aims to analyze the influence of self-awareness and involvement in the morning apple on the work discipline of the State Civil Apparatus (ASN) at the Jombang Regency Education and Culture Office. Work discipline is a fundamental aspect in the performance of ASN because it reflects responsibility, integrity, and professionalism in carrying out public service duties. Self-awareness is an internal factor that encourages individuals to understand the value, role, and consequences of each action in the work environment. Meanwhile, involvement in the morning apple is a form of collective activity that fosters a sense of togetherness, shared responsibility, and compliance with organizational rules. This study uses a quantitative approach with a total of 104 ASN respondents selected through the proportionate stratified random sampling technique. Data collection was carried out using a closed questionnaire with a Likert scale, then analyzed using multiple linear regression through the SPSS program to determine the partial and simultaneous influence between variables. The results showed that self-awareness had a positive and significant effect on ASN's work discipline (β = 1.009; t = 2.704; sig. = 0.018). Similarly, involvement in morning apples had a positive and significant effect on ASN's work discipline (β = 0.959; t = 2.402; sig. = 0.008). Simultaneously, the two variables had a significant influence on work discipline (F = 22.112; sig. = 0.000) with a determination coefficient (R²) of 0.291, which means that 29.1% variation in ASN work discipline can be explained by these two variables.These findings confirm that the formation of self-awareness and increased participation in the morning apple is an effective strategy in strengthening the culture of ASN work discipline. Therefore, public organizations need to integrate mental coaching activities and collective discipline on an ongoing basis to create civil servants with integrity, productivity, and oriented towards quality public services.